Real-world clinical effectiveness of trimethoprim–sulfamethoxazole for primary prophylaxis of pneumocystis pneumonia in non-hodgkin lymphoma patients treated with rituximab - Patcharaporn Charoenrit; Pimjai Niparuck; Porpon Rotjanapan (PLoS ONE, 2026)
There are no definitive clinical practice guidelines regarding the necessity and dosage of trimethoprim–sulfamethoxazole (TMP/SMX) prophylaxis for Pneumocystis jirovecii pneumonia (PJP) in individuals undergoing rituximab therapy. This retrospective study evaluated the effectiveness and safety of various TMP–SMX prophylactic dosing regimens over a 1-year period in 690 patients with non-Hodgkin lymphoma treated with rituximab at a university hospital in Thailand from 2013 to 2022. Out of these patients, 622 (90.1%) received TMP/SMX, with a mean duration of prophylaxis of 265.7 days (SD 85.66). The overall incidence of PJP was 1% (7 patients), which was significantly higher in the non-prophylaxis group (5.8%, 4 patients) compared to the prophylaxis group (0.6%, 3 patients). No cases of PJP occurred among those receiving standard prophylaxis or a single-strength tablet every other day, three times a week. However, instances in the prophylaxis cohort were reported in patients who took two single-strength tablets twice daily, twice a week. Prophylaxis resulted in a significant reduction in the one-year incidence of PJP, with a hazard ratio of 0.105 (95% CI: 0.023–0.469). Mild adverse reactions were noted in 3.05% of patients, all of whom recovered. These findings suggest that TMP/SMX prophylaxis was associated with a lower incidence of PJP and was well tolerated. Future studies should explore optimal dosing strategies while considering patient selection bias and concurrent immunosuppressive therapy.